(untitled) (Research, Society and Development, 2022)
Objective: to know the view of the nursing team of a philanthropic hospital about the supervision of the service. Methodology: it was characterized as a descriptive study of qualitative approach, carried out in a philanthropic hospital located in the northern region of Minas Gerais, having as participants 14 nursing professionals (technicians and nurses). For data collection, a semi-structured interview script was used and bardin’s thematic content analysis technique was predefined. Results: Through the results emerged the following categories: nursing supervision, activities developed by the nursing supervisor, facilitators and facilitators of nursing supervision. The reports of the study participants showed partial knowledge about nursing supervision, however they recognized the importance for quality care. As for the activities performed by the supervisor, there was a predominant picture of activities focused on the bureaucratic part and overload of this professional with multifunctions, with adequate supervision. Conclusion: the professionals’ reports evidenced a partial view or knowledge about nursing supervision, presenting difficulties that can influence the work process.